Condicionamento fisiológico e conservação de sementes de tabaco - Lopes, Camila Aparecida (2019)
Seeds priming or conditioning are commercial techniques that allows standardize and reduce the time of germination and emergence of seedlings, but its effect is influenced by several factors such as: conditioning time, conditioning agent, species, cultivar and initial physiological seed lot quality. In addition, it presents as possible limitation the seed quality loss and the benefits of treatment throughout the storage. Four experiments were carried out with the objective of analyzing methodologies for the tobacco seeds priming, defining the most suitable conditioning agent and evaluating different storage forms (cold room and cryopreservation) for the maintenance of the physiological quality of conditioned seed lots from different vigor levels. According to the results, the priming with sodium hypochlorite does not affect the percentage of germination, but it allows a greater speed and emergence of seedlings when using the concentration 1% for 180, 30 and 15 minutes. The conditioning agent, initial lot quality and storage time interfere with the physiological quality of conditioned tobacco seeds stored in a cold room. Water, spermidine (0.5 mmol.L−1) and potassium nitrate (-1 MPa) are suitable conditioning agents for the tobacco seeds priming that can be maintained after conditioning in a cold room at 10 °C for sixteen months without loss of its physiological quality. The conditioning provides greater activity of the enzymes catalase, esterase, alcohol dehydrogenase and malate dehydrogenase until the 12th month of storage. Tobacco seeds conditioned to spermidine and water can be cryopreserved without loss of initial physiological quality when they are rapidly dried on silica gel and reheated in a water bath for 2 minutes.